2021
DOI: 10.1021/acs.joc.1c00590
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Approach for Construction of 5,6-Dihydroimidazo[2,1-a]isoquinolines and Their Luminescent Properties

Abstract: A visible-light-driven photoredox reaction of tetrahydroisoquinoline with 2H-azirines is described. 4,7-Bis­(4-methoxy­phenyl)­benzo­[c]­[1,2,5]­thiadiazole, a benzothiadiazole (BTD) derived fluorophore, is used as an organic photoredox catalyst, and the reaction offers an efficient access to 5,6-dihydro­imidazo­[2,1-a]­isoquinolines with a broad range of functional groups. The resulting 5,6-dihydro­imidazo­[2,1-a]­isoquinolines present strong photoluminecence in solutions and powders and could be applied in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Further solvent survey indicated that DCE remained the preferred solvent among the tested solvents including toluene, CH 2 Cl 2 , CHCl 3 , THF, 1,4-dioxane, and diethyl ether (entries 5-10). Screening of phosphine reagents showed that P(n-Bu) 3 , P(t-Bu) 3 and PMePh 2 all provided poor yields (entries [11][12][13]. Phosphite P(OMe) 3 was completely ineffective in the reaction (entry 14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further solvent survey indicated that DCE remained the preferred solvent among the tested solvents including toluene, CH 2 Cl 2 , CHCl 3 , THF, 1,4-dioxane, and diethyl ether (entries 5-10). Screening of phosphine reagents showed that P(n-Bu) 3 , P(t-Bu) 3 and PMePh 2 all provided poor yields (entries [11][12][13]. Phosphite P(OMe) 3 was completely ineffective in the reaction (entry 14).…”
Section: Resultsmentioning
confidence: 99%
“…3 b , c ,9 For example, under the irradiation of visible light and under the catalysis of [Ru(bpy) 3 ][(PF 6 ) 2 ] or benzothiadiazole (BTD) derivative, photocatalytic formal [3 + 2] annulation reactions of 2 H -azirines with tetrahydroisoquinolines occur via C3N bond cleavage (Scheme 1, c). 10,11 Therefore, in the development of green syntheses of heterocycles, 2 H -azirines have exhibited versatile photochemical reactivity. Intrigued by the reported photochemical reactivity of 2 H -azirines in formal [3 + 2] annulation reactions, also considering the diverse reactivity of Huisgen zwitterions in the carbon–nitrogen bond forming reactions, 12 we envisioned that, under the light irradiation, azirines would couple with in situ generated Huisgen zwitterions to form three-nitrogen-containing heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…It was noted that the cycloaddition yields were lower when R 1 were alkyls than that of aryls, which was consistent with that previously reported. 8,10…”
Section: Resultsmentioning
confidence: 99%
“…Because of these properties, they have become valuable building blocks in organic and medicinal chemistry. 5 Visible light-induced reactions using 2 H -azirines as substrates have been developed to synthesize various nitrogen-containing heterocycles (Scheme 1), such as oxazoles, 6 triazoles, 7 dihydro-oxadiazoles, 8 triazines, 9 dihydroimidazo[2,1- a ]isoquinolines, 10 benzo[ f ]isoindole-4,9-diones 11 and pyrroles. 12 Although there are many reported cyclizations of 2 H -azirines that proceed via light-induced pathways, light-induced diastereoselective transformations of 2 H -azirines remain unexplored; there are few examples of a diastereoselective transformation that proceeds via ring opening of 2 H -azirines under light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…5 While there has been selected reports of homogeneous BTZ photocatalysis arising from intramolecular charge transfer between the donor and acceptor units, there has been no indepth exploration of how their photophysical properties and excited state redox potentials can be altered by manipulating available structural levers. [30][31][32][33][34][35] The reaction that was selected to test this library of BTZ photocatalysts was the decarboxylative C-H functionalisation of heteroarenes, previously explored by Glorius and coworkers. 36 This Miniscitype reaction was noted to provide a direct method to alkylate a wide variety of substrates, including pharmaceutical analogues, using visible light and without the need for prefunctionalisation of substrates.…”
Section: Introductionmentioning
confidence: 99%